Utilization of agro-industrial waste to improve thermal behavior of products made of fired clay for traditional masonry (2021)
The reutilization of agro-industrial waste in the manufacture of fired clay products is a sustainable strategy that aims at the circular economy. The most known waste in Norte de Santander, Colombia, are coffee husk and rice husk. For this reason, this research studies the thermal impact of their insulating properties in traditional masonry products made of fired clay to be considered as insulating additives. The methodology involves the simulation of heat transfer and heat flux of the multiperforated brick and H10 block manufactured in mixtures of 100% clay and 95% clay and 5% additive to wastes in North Santander, Colombia, in the software ANSYS under the finite element method in extreme conditions of San José de Cúcuta. The results demonstrate that the residues of rice husk and coffee husk act as insulating technological nutrients with a reduction of temperatures of the interior surfaces of the products between 0.22 °C and 0.88 °C, respectively. The reutilization of residual raw materials from alternate construction industries is a sustainable consideration to evaluate new possibilities for the manufacture of products with less embedded energy and, therefore, with a lower carbon footprint than traditional fired clay products.